Model based scattering correction in time-of-flight cameras - Schäfer, Henrik; Lenzen, Frank; Garbe, Christoph S. (Optics express, 2014)
In-camera light scattering is a systematic error of Time-of-Flight depth cameras that significantly reduces the accuracy of the systems. A completely new model is presented, based on raw data calibration and only one additional intrinsic camera parameter. It is shown that the approach effectively removes the errors of in-camera light scattering.
Gesehen am 05.11.2020